DESCRIPTION OF PERCEPTION OF MEDICAL STUDENTS IN ANDALAS UNIVERSITY TOWARD INTERPROFESSIONAL EDUCATION (IPE) - Sari, Anisha Purnama; Isrona, Laila; Afriani, Nita; Burhan, Ida Rahmah; Elmatris, Elmatris; Windasari, Noverika (SINERGI : Jurnal Riset Ilmiah, 2025)
Interprofessional Education (IPE) is a pedagogical approach to prepare clinical students to provide health services to patients in a collaborative and integrated manner in order to improve the quality of health services through the implementation of Interprofessional Collaboration (IPC). The purpose of this study was to describe the perceptions of medical students of FK UNAND towards IPE. This research is a descriptive study with a quantitative approach. Cross sectional design is used for the research. This study used the Interdisciplinary Education Perception Scale (IEPS) questionnaire which was distributed via Google form with a total sample of 258 medical students in the period October 2022 – January 2023. The research sample was determined using a proportionate stratified random sampling technique. A total of 231 students (89,5%%) had a good perception of IPE with the component of perceived need for cooperation having the highest percentage (95,7%) and component of understanding others’ value having the lowest percentage (62,4%%). Clinical students of 2020 have the highest perception percentage of all the other years (90,6%), followed by the clinical students of 2021 (89,1%), and lastly the clinical students of 2022 with the lowest percentage of perception (88,8%). The perception of medical students of FK UNAND towards IPE is mostly in the good category, however, component of understanding others’ value is still lacking and therefore needs to be improved. The abstract is presented in both Bahasa Indonesia and English.